Spectrophotometric Determination of Profenofos Using an Aptamer-Gold Nanorod (GNR)-Based Biosensor. (13th June 2023) - Lu, Zhufeng; Li, Jiayou; Shen, Jie; Wang, Hongmei
Abstract: A biosensor based on the optical signal of gold nanorods (GNRs) and an aptamer as the recognition element is reported to perform the rapid and selective spectrophotometric determination of profenofos. The GNR synthesized by the seed growth method have unique structures which binds with the aptamer through electrostatic adsorption and is well dispersed in a salt-containing solution. Upon the addition of profenofos, specific recognition caused aggregation of the GNRs. The optical signal therefore decreased and the response linearly related to the concentration of profenofos. The results demonstrate that ascorbic acid as the reducing agent plays an important role in the morphology of the GNRs. GNRs with the length- diameter ratio (L/D) of 12 stably combined with the aptamer. For the optimum conditions, spectrophotometric determination of profenofos was achieved using the biosensor with a linear relationship between the absorbance of GNR at 508 nm and the concentration of profenofos from 40 to 460 µg/L. The limit of detection of the method was 31.93 µg/L. In addition, this approach shows good selectivity for the analysis of fruits and vegetable. A valuable new method is reported for the determination of profenofos.